2018
DOI: 10.1097/ccm.0000000000002993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emergency Department and ICU Occupancy on Admission Decisions and Outcomes for Critically Ill Patients*

Abstract: ICU admission decisions for critically ill emergency department patients are affected by medical ICU bed availability, though higher emergency department volume and other ICU occupancy did not play a role. Prolonged emergency department boarding times were associated with worse patient outcomes, suggesting a need for improved throughput and targeted care for patients awaiting ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 49 publications
5
61
2
Order By: Relevance
“…Other common diseases may require critical care in the ED prior to admission, including diabetic ketoacidosis, metabolic derrangements, gastrointestinal hemorrhage, and neurovascular disorders. Unfortunately, the boarding of critically ill patients in the ED is associated with delays in care, which impact broad clinical outcomes in the critically ill 16‐20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other common diseases may require critical care in the ED prior to admission, including diabetic ketoacidosis, metabolic derrangements, gastrointestinal hemorrhage, and neurovascular disorders. Unfortunately, the boarding of critically ill patients in the ED is associated with delays in care, which impact broad clinical outcomes in the critically ill 16‐20 …”
Section: Resultsmentioning
confidence: 99%
“…This lack of standardization precludes meaningful aggregation of data or comparisons between published results. Some studies describe boarding as total time spent in the ED 18,20‐26 , with some defining that time only after the decision to admit 18,20,26 . One study required that ICU beds be unavailable for ED boarding to occur, 27 whereas another used the distribution of ED wait times to define outliers 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that each hour of delay independently associates with increased risk of ICU mortality and that delays of 4‐6 hours increase mortality . One recent study showed that in addition to increased mortality, longer stay at the ED is associated with more persistent organ dysfunction . However, there are also other studies with no effect on outcome .…”
Section: Discussionmentioning
confidence: 99%
“…A 3‐hour cutoff value for delayed ICU admission has been used in an earlier study investigating the effect of delayed ICU admission on outcome . The effect of delayed admission on patient outcome has been controversial with either no association in critically ill patients or with worse patient outcome …”
Section: Introductionmentioning
confidence: 99%
“…Because hospitals are increasingly burdened with crowding, boarding of critically ill patients in the ED has become increasingly common. 1,2 Studies have shown that prolonged boarding of critically ill patients in the ED is associated with increased morbidity and mortality. 1,2 Moreover, among intubated patients, there is increasing recognition that the management of nonventilator components influences patient outcomes.…”
Section: Commentarymentioning
confidence: 99%